2019
DOI: 10.1124/pr.119.017681
|View full text |Cite
|
Sign up to set email alerts
|

Druggable Transcriptional Networks in the Human Neurogenic Epigenome

Abstract: Chromosome conformation capture methods have revealed the dynamics of genome architecture which is spatially organized into topologically associated domains, with gene regulation mediated by enhancer-promoter pairs in chromatin space. New evidence shows that endogenous hormones and several xenobiotics act within circumscribed topological domains of the spatial genome, impacting subsets of the chromatin contacts of enhancer-gene promoter pairs in cis and trans. Results from the National Institutes of Health-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 162 publications
(238 reference statements)
0
12
0
Order By: Relevance
“…SMARCA-deficiencies are associated to several malignancies and birth defects; its homozygous loss lead to embryo lethality (Pulice and Kadoch, 2016). Valproic acid is known to alter the expression of SMARCA4 and SMARCD1 in neuroblastoma cells (Hu et al, 2020), and SMARCA genes are suggested as members of the neurogenic transcriptional network control (Higgins et al, 2019). Hence, valproate-induced perturbances in SMARCA genes might be sufficiently disruptive to explain Fetal Valproate Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA-deficiencies are associated to several malignancies and birth defects; its homozygous loss lead to embryo lethality (Pulice and Kadoch, 2016). Valproic acid is known to alter the expression of SMARCA4 and SMARCD1 in neuroblastoma cells (Hu et al, 2020), and SMARCA genes are suggested as members of the neurogenic transcriptional network control (Higgins et al, 2019). Hence, valproate-induced perturbances in SMARCA genes might be sufficiently disruptive to explain Fetal Valproate Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This research emphasizes the role of the regulatory genome, including enhancer and superenhancer-based interactomes, as an approach that provides insight into pharmacogenomic network mechanisms (22)(23)(24)(25). It differs from pathway modeling methods in which altered protein folding based on missense codon variants and fixed signaling pathways serve as the foundation for the interpretation of the molecular substrate of ketamine response in humans.…”
Section: The Ketamine Pharmacogenomic Sub-networkmentioning
confidence: 99%
“…The ketamine response workflow is based on the pharmacoepigenomics informatics pipeline (PIP) (22)(23)(24)(25). Input genes to the data analysis pipeline first included those genes that encode proteins and constituents of macromolecular protein complexes obtained from past studies of the binding affinity of (R, S)-ketamine, R-ketamine and S-ketamine performed in microsomal and tissue preparations in rodents and humans.…”
Section: Selection Of Ketamine-response Genesmentioning
confidence: 99%
See 2 more Smart Citations